(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The present study is concerned with the importance of Empowerment and investing it as a development strategy to enhance the creativity of employees in the Diwaniyah tires plant, as it is a strategic dimension that enables the organization to achieve a competitive position by motivating employees to research and development to enhance their creativity and adoption of new and unusual ideas that result in changes in their favor creativity as an effective tool for the success and sustainability of the organization. To achieve the objectives of the study, a questionnaire of (40) item adopted, The sample included (75) workers from different levels of the organization. According to the purpose of the study, two main hypotheses were formulated. A range of statistical means has been used by Using on (spss vr.24). The researcher came up with a set of conclusions and recommendations that are consistent with those conclusions: The responses of the sample respondent reflected a Positive trend of the importance of Empowerment as a Vital Strategy in Order to establish the foundation of development and Creativity and adopt a successful business philosophy in order to upgrade the Organization.